A Novel Nomogram for Predicting Post-Operative Sepsis for Patients With Solitary, Unilateral and Proximal Ureteral Stones After Treatment Using Percutaneous Nephrolithotomy or Flexible Ureteroscopy - Sun, Jian-Xuan; Xu, Jin-Zhou; Liu, Chen-Qian; Xun, Yang; Lu, Jun-lin; Xu, Meng-Yao; An, Ye; Hu, Jia; Li, Cong; Xia, Qi-Dong; Wang, Shao-Gang (Frontiers in Surgery, 2022)
Background The postoperative sepsis is a latent fatal complication for both flexible ureteroscopy (fURS) and percutaneous nephrolithotomy (PNL). An effective predictive model constructed by readily available clinical markers is urgently needed to reduce postoperative adverse events caused by infection. This study aims to determine the pre-operative predictors of sepsis in patients with unilateral, solitary, and proximal ureteral stones after fURS and PNL. Methods We retrospectively enrolled 910 patients with solitary proximal ureteral stone with stone size 10–20 mm who underwent fURS or PNL from Tongji Hospital's database, including 412 fURS cases and 498 PNL cases. We used the least absolute shrinkage and selection operator (LASSO) regression and multivariate logistic regression analysis to identify the risk factors for sepsis. Finally, a nomogram was assembled utilizing these risk factors. Results In this study, 49 patients (5.4%) developed sepsis after fURS or PNL surgery. Lasso regression showed postoperative sepsis was associated with gender (female), pre-operative fever, serum albumin (<35 g/L), positive urine culture, serum WBC (≥10,000 cells/ml), serum neutrophil, positive urine nitrite and operation type (fURS). The multivariate logistic analysis indicated that positive urine culture (odds ratio [OR] = 5.9092, 95% CI [2.6425–13.2140], p < 0.0001) and fURS (OR = 1.9348, 95% CI [1.0219–3.6631], p = 0.0427) were independent risk factors of sepsis and albumin ≥ 35g/L (OR = 0.4321, 95% CI [0.2054–0.9089], p = 0.0270) was independent protective factor of sepsis. A nomogram was constructed and exhibited favorable discrimination (area under receiver operating characteristic curve was 0.78), calibration [Hosmer–Lemeshow (HL) test p = 0.904], and net benefits displayed by decision curve analysis (DCA). Conclusions Patients who underwent fURS compared to PNL or have certain pre-operative characteristics, such as albumin <35 g/L and positive urine culture, are more likely to develop postoperative sepsis. Cautious preoperative evaluation and appropriate operation type are crucial to reducing serious infectious events after surgery, especially for patients with solitary, unilateral, and proximal ureteral stones sized 10–20 mm.